Al-Mn-Sc-Zr aluminum alloy system for additive manufacturing and powder preparation method of Al-Mn-Sc-Zr aluminum alloy system

Through the composite addition of Sc and Zr and the synergistic effect of Mg and Si elements, fine nano or microparticle phases are generated, which solves the problems of large residual stress and insufficient tensile strength in additive manufacturing of Al-Mn alloys, and realizes a high-strength, high-strength, high-strength, and low-cracking aluminum alloy system.

CN119859769APending Publication Date: 2025-04-22NANJING TECH UNIV

Patent Information

Application Number
CN202510112262.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The existing Al-Mn alloy system has problems such as large residual stress and easy cracking during the additive manufacturing process, and the tensile strength after heat treatment is not enough to meet the use requirements.

Method used

Primary Al3 (Sc,Zr) particles were generated by Sc and Zr composite addition, Mg and Si composite addition generated Mg2Si, Mg5Si6 and other particle phases. After the pre-alloyed preform ingot was prepared, powder preparation and laser melting were carried out to form fine micron or nanoparticles, and the mechanical properties of the alloy were improved by aging treatment.

Benefits of technology

Aluminum alloy system with high strength, high toughness and low cracking tendency has been achieved, with tensile strength reaching more than 580MPa and density reaching more than 99.9%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859769A_ABST
    Figure CN119859769A_ABST
Patent Text Reader

Abstract

The invention discloses Al-Mn-Sc-Zr aluminum alloy powder for additive manufacturing, which is prepared from the following components in percentage by mass: 4.0 to 7.0 percent of Mn, 0.5 to 3.0 percent of Mg, 0.2 to 1.5 percent of Cu, 0.05 to 0.2 percent of Ti, 0.4 to 1.0 percent of Sc, 0.2 to 0.8 percent of Zr, 0.2 to 0.8 percent of Si, less than 0.15 percent of Fe and the balance of A1 and unremovable impurities. The preparation method comprises the following steps: 1, smelting and casting a master ingot alloy; secondly, the alloy master ingot is prepared into powder through vacuum gas atomization or prepared into a wire through a rolling technology; and thirdly, powder or wire material additive printing is conducted on the component. The tensile strength of a component printed by the powder prepared by the method through laser melting reaches 580 MPa or above, the percentage elongation after fracture reaches 12% or above, and the compactness of a workpiece can reach 99.9% or above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of additive manufacturing powder preparation, in particular to an Al-Mn-Sc-Zr aluminum alloy system for additive manufacturing and a powder preparation method thereof. Background Art

[0002] As one of the most representative manufacturing methods of additive manufacturing, laser melting (SLM) is developed based on selective laser sintering. Under the irradiation of high-energy laser beam, the metal powder melt pool exchanges heat with the matrix at a very fast speed, and finally solidifies and forms quickly. The laser melting process has the characteristics of high forming accuracy, stable internal structure, and excellent mechanical properties. The cooling rate of the equipment can reach 1×10 7 K / s, the structural parts formed by this rapid cooling have finer grains than those formed by traditional casting manufacturing methods, and only require a small amount of surface treatment in the later stage before use. At the same time, compared with traditional casting, the digital SLM process is more flexible and convenient, and can protect the environment and effectively save resources while ensuring the integrity of parts. This technology has been successfully applied to the production and manufacturing of aluminum alloy parts. It is one of the most promising process technologies for the preparation of fine and complex metal structural parts, and will have a revolutionary impact on the fields of aerospace, automobiles, ships, and medical care.

[0003] With the application and promotion of Al-Mg-Sc-Zr (Scalmalloy®) designed and developed by Airbus for SLM, domestic and foreign scholars have increased their research interest in SLM Al-Mg-Sc-Zr. For example, existing patent 1 (CN107502795A) and existing patent 2 (CN115354199A) involve laser melting of Al-Mg-Sc-Zr alloy. The invention uses Sc and Zr as strengthening elements. During the laser melting process, Sc and Zr combine to form a stable strengthening phase, which will increase the recrystallization temperature of the aluminum alloy material and refine the grains. However, the tensile strength of the aluminum alloy after heat treatment does not exceed 500MPa. From the strengthening mechanism, the solid solution strengthening effect of Mn atoms in aluminum alloy is better than that of Mg atoms. The disadvantage is that the laser melting of Al-Mn alloy has high printing stress and is prone to microcracks. Therefore, some experts have carried out SLM Al-Mn-Sc-Zr system aluminum alloy based on the research ideas of SLM Al-Mg-Sc-Zr alloy, but have not obtained ideal mechanical properties. Existing patent 3 (CN115141955A) and existing patent 4 (CN114277285B) involve an Al-Mn-Sc-Zr alloy for 3D printing. Both methods use Mn as the main strengthening element, Mg element as auxiliary strengthening, and Sc and Zr are added in combination. The formed Al3 (Sc, Zr) particles can significantly refine the grains, ensuring high density, crack-free and certain corrosion resistance of the printed structural parts. However, the mechanical properties after heat treatment are significantly different from those of Airbus' Al-Mg-Sc-Zr (Scalmalloy®) alloy, and the final tensile strength is only 480MPa, which cannot meet the use requirements. Summary of the invention

[0004] In view of the problems of large residual stress and easy cracking in the additive manufacturing process in the existing Al-Mn alloy system, the purpose of the present invention is to develop a new type of high-strength, high-toughness, low-cracking tendency aluminum alloy system for additive manufacturing that can be aged and strengthened by multiple precipitation phase coupling, as well as a matching powder preparation method and printing process. Primary Al3 (Sc, Zr) particles are generated by composite addition of Sc and Zr, and Mg and Si are generated by composite addition of Mg2Si, Mg5Si6 and other particle phases, which play a role in grain refinement of pre-alloyed mother ingots, and form finer micron or nanoparticles in the subsequent powder preparation and rapid cooling process of additive manufacturing. After aging treatment, the above-mentioned nano-precipitated particles play a role in precipitation strengthening and pinning dislocations on the alloy, coupling and strengthening the mechanical properties of the alloy, and the tensile strength reaches more than 580MPa.

[0005] To achieve the above object, the present invention provides the following technical solutions: In the first aspect, the present invention discloses an Al-Mn-Sc-Zr aluminum alloy powder for additive manufacturing, which is composed of the following components by mass percentage: Mn: 4.0-7.0%, Mg: 0.5-3.0%, Cu: 0.2-1.5%, Ti: 0.05-0.2%, Sc: 0.4-1.0%, Zr: 0.2-0.8%, Si: 0.2-0.8%, Fe: <0.15%, and the rest is Al and non-removable impurities. The mass percentage ratio of Sc and Zr elements in the aluminum alloy powder is 2:1.

[0006] Preferably, the present invention provides an Al-Mn-Sc-Zr aluminum alloy system powder for additive manufacturing, which is composed of the following components by mass percentage: Mn: 4.5~5.5%, Mg: 1.0~1.5%, Cu: 0.2~1.5%, Ti: 0.05~0.2%, Sc: 0.4~1.0%, Zr: 0.2~0.5%, Si: 0.5~0.8%, Fe: <0.1%, and the rest are A1 and non-removable impurity elements.

[0007] More preferably, by mass percentage, Mg+Si≥1.85%, Sc+Zr≥0.6%.

[0008] In a second aspect, the present invention provides a method for preparing Al-Mn-Sc-Zr aluminum alloy system powder for additive manufacturing, comprising the following steps: (1) Add pure aluminum ingots into the crucible in the medium frequency furnace at a temperature of 460°C; (2) Raise the temperature of the smelting chamber to 720°C~740°C until the pure aluminum ingot is melted; (3) Raise the temperature to 740-760°C, add Al-10Mn, Al-50Cu, Al-20Si and Al-5Ti master alloys to the resistance furnace in turn, keep warm for 10 min, then add A1-2Sc master alloy and Al-5Zr master alloy in turn, keep warm for 30 min after they are completely melted; (4) Lower the power of the medium frequency furnace to reduce the temperature to 710~720℃ and add pure magnesium ingot; (5) After the magnesium ingot is completely melted, keep it warm for 10 minutes, add 0.1% by mass of Al-Ti-B wire to obtain molten aluminum alloy liquid; (6) The molten aluminum alloy is water-cooled and semi-continuously cast into a prefabricated alloyed mother ingot with a specification of φ90mm-φ720.

[0009] The composite material system mother ingot of the present invention is made into powder or wire, and the alloyed mother ingot is made into powder for laser melting printing or wire for arc additive manufacturing. Other powders can also be prepared according to the use of the powder.

[0010] The particle size of the powder can also be prepared according to needs, including 1-15μm, 15-53μm, 53-150μm. The wire can be prepared according to needs, and the arc additive can be obtained by continuous casting, continuous extrusion, etc. φ2-φ9mm.

[0011] When the composite material system mother ingot is made into powder, it also includes sawing the prefabricated alloyed mother ingot into small pieces, melting the prefabricated alloyed small pieces of mother ingot at 700°C~760°C in a melting crucible by vacuum gas atomization powder making, preparing alloy melt, and obtaining prefabricated alloy metal powder after gas atomization cooling.

[0012] Furthermore, the specific steps of vacuum gas atomization are as follows: evacuate the vacuum atomization melting chamber to 0~10 -2 Pa, argon gas is used for replacement treatment to keep the gas pressure between 0.5 and 6 MPa.

[0013] Furthermore, the atomizing gas pressure is in the range of 0.5MPa to 4MPa.

[0014] Furthermore, the molten alloy liquid is passed through a nozzle, crushed by atomized argon gas under high pressure, and then cooled and spheroidized to obtain aluminum alloy metal powder.

[0015] Furthermore, the aluminum alloy metal powder is cooled to 25° C. to 60° C., screened in an argon atmosphere, and then vacuum packaged.

[0016] Furthermore, the particle size ranges after screening are 1-15 μm, 15-53 μm, and 53-150 μm.

[0017] The invention also discloses the application of powder in laser melting, wherein the powder with a particle size range of 15-53 μm after screening is subjected to aging heat treatment after laser melting to obtain a final molded part.

[0018] Beneficial Effects of the Invention 1) In the present invention, the pre-alloyed mother ingot is used to prepare the initially dispersed nano or micron particle phase, which plays a role in grain refinement. These precipitated phases are further refined during the subsequent rapid solidification of the molten droplets and laser melting, ensuring a sufficient number of nucleation points while promoting grain refinement.

[0019] 2) Aiming at the problem of microcracks and holes in Al-Mn alloy prepared by laser melting, the present invention adds Sc and Zr, Cu and Ti elements in specific proportions, controls the number of nano-nucleation particles Al3(Sc, Zr) and Al3Ti in a single molten pool during the printing process, induces grain refinement, promotes the increase of grain boundary density, and thus inhibits the formation of microcracks; at the same time, the addition of the above proportion elements and a small amount of Si element reduces the melt viscosity. According to the viscosity-driven mechanism, they reduce the tendency of pore formation at the tip of the keyhole, play a role in inhibiting the formation of microholes, and further reduce the phenomenon of microcrack initiation caused by stress concentration at the hole, thereby inhibiting the formation of microcracks. The density of the molded part can reach more than 99.9%.

[0020] 3) In order to solve the problem of insufficient precipitated phases in the preparation process of conventional Al-Mn-Sc-Zr alloy system, the present invention adds Mg, Cu, Ti and Si elements to generate Al3Ti, Mg2Si, Mg5Si6 and other particle phases through alloying. These phases work together with Al6Mn and Al3(Sc, Zr) to couple-strengthen Al-Mn-Sc-Zr alloy by pinning dislocations and grain boundaries, thereby improving the mechanical properties of the alloy. After direct aging, the tensile strength exceeds 580MPa, and the elongation after fracture exceeds 12%. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 is the metallographic diagram of Comparative Examples 1, 2, Examples 3 and 4; wherein Figure 1 (a) is the metallographic image of the alloy obtained in Comparative Example 1, Figure 1 (b) is the metallographic image of the alloy obtained in Comparative Example 2, Figure 1 (c) is the metallographic image of the alloy obtained in Example 3, Figure 1 (d) is the metallographic image of the alloy obtained in Example 4; Figure 2 This is the SEM picture of Example 3. DETAILED DESCRIPTION

[0022] The present invention is described in detail below in conjunction with the accompanying drawings and embodiments. This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments.

[0023] Example 1 Laser melted Al-Mn-Sc-Zr alloy powder has a composition of Mn: 4.5%, Mg: 1.5%, Sc: 0.4%, Zr: 0.2%, Cu: 0.2%, Ti: 0.2%, Si: 0.5%, and the rest are Al and unremovable impurity elements.

[0024] Preparation of mother ingot: add pure aluminum ingot to the crucible in the medium frequency furnace at a temperature of 460°C; raise the temperature of the smelting chamber to 740°C until the pure aluminum ingot is melted; raise the temperature to 760°C, add Al-10Mn, Al-50Cu, Al-20Si and Al-5Ti to the resistance furnace, and keep warm for 10 minutes; then add A1-2Sc master alloy and Al-5Zr master alloy in sequence, and keep warm for 30 minutes after they are completely melted; reduce the power of the medium frequency furnace to reduce the temperature to 720°C, and add pure magnesium ingot at the same time; after the magnesium ingot is completely melted, keep warm for 10 minutes, add 0.1% by mass of Al-Ti-B wire to obtain molten aluminum alloy liquid; cast the molten aluminum alloy liquid into a prefabricated alloyed mother ingot with a specification of φ90mm and a height of 300mm; Powder preparation: Saw the alloy prefabricated master ingot into small pieces, melt the prefabricated alloy small master ingot at 740℃ in a melting crucible by vacuum gas atomization powder making to prepare alloy melt. Evacuate the vacuum atomization melting chamber to 4*10 -2 Pa, argon gas is used for replacement treatment to keep the gas pressure at 1.5MPa; the molten alloy liquid passes through a nozzle, is crushed by gas atomization argon gas high pressure, and then is cooled and spheroidized to obtain aluminum alloy metal powder; the aluminum alloy metal powder is cooled to 50°C, sieved in an argon atmosphere, and then vacuum packaged; Laser melting: The powder with a particle size range of 15-53 μm after screening was subjected to aging heat treatment after laser melting to obtain the final molded part. A 10 mm × 10 mm × 10 mm cubic block was printed, and the alloy hardness was measured using a microhardness tester. After direct aging at 325 ° C / 6 h, the mechanical properties were tested using an ETM105D universal testing machine with a tensile rate of 1 mm / min.

[0025] Example 2 Laser melted Al-Mn-Sc-Zr alloy powder has a composition of Mn: 4.5%, Mg: 1.5%, Sc: 0.6%, Zr: 0.3%, Cu: 0.2%, Ti: 0.2%, Si: 0.6%, and the rest are Al and unremovable impurity elements, by mass percentage.

[0026] Preparation of mother ingot: add pure aluminum ingot to the crucible in the medium frequency furnace at a temperature of 460°C; raise the temperature of the smelting chamber to 720°C until the pure aluminum ingot melts; raise the temperature to 740°C, add Al-10Mn, Al-50Cu, Al-20Si and Al-5Ti to the resistance furnace, and keep warm for 10 minutes; then add A1-2Sc master alloy and Al-5Zr master alloy in sequence, and keep warm for 30 minutes after they are completely melted; reduce the power of the medium frequency furnace to reduce the temperature to 710°C, and add pure magnesium ingot at the same time; after the magnesium ingot is completely melted, keep warm for 10 minutes, add 0.1% by mass of Al-Ti-B wire to obtain molten aluminum alloy liquid; cast the molten aluminum alloy liquid into a prefabricated alloyed mother ingot with a specification of φ90mm and a height of 300mm; Powder preparation: Saw the alloy prefabricated master ingot into small pieces, melt the prefabricated alloyed master ingot at 740℃ in a melting crucible by vacuum gas atomization to prepare alloy melt. Evacuate the vacuum atomization melting chamber to 2*10 -2 Pa, argon gas is used for replacement treatment to keep the gas pressure at 2.0MPa; the molten alloy liquid passes through a nozzle, is crushed by gas atomization argon gas high pressure, and then is cooled and spheroidized to obtain aluminum alloy metal powder; the aluminum alloy metal powder is cooled to 30°C, sieved in an argon atmosphere, and then vacuum packaged; Laser melting: The powder with a particle size range of 15-53 μm after screening was subjected to aging heat treatment after laser melting to obtain the final molded part. A 10 mm × 10 mm × 10 mm cubic block was printed, and the alloy hardness was measured using a microhardness tester. After direct aging at 325 ° C / 6 h, the mechanical properties were tested using an ETM105D universal testing machine with a tensile rate of 1 mm / min.

[0027] Example 3 Laser melted Al-Mn-Sc-Zr alloy powder has a composition of Mn: 5.0%, Mg: 1.35%, Sc: 0.8%, Zr: 0.4%, Cu: 0.5%, Ti: 0.05%, Si: 0.8%, and the rest are Al and unremovable impurity elements, by mass percentage.

[0028] Preparation of mother ingot: add pure aluminum ingot to the crucible in the medium frequency furnace at a temperature of 460°C; raise the temperature of the smelting chamber to 720°C until the pure aluminum ingot is melted; raise the temperature to 760°C, add Al-10Mn, Al-50Cu, Al-20Si and Al-5Ti to the resistance furnace, and keep warm for 10 minutes; then add A1-2Sc master alloy and Al-5Zr master alloy in sequence, and keep warm for 30 minutes after they are completely melted; reduce the power of the medium frequency furnace to reduce the temperature to 720°C, and add pure magnesium ingot at the same time; after the magnesium ingot is completely melted, keep warm for 10 minutes, add 0.1% by mass of Al-Ti-B wire to obtain molten aluminum alloy liquid; cast the molten aluminum alloy liquid into a prefabricated alloyed mother ingot with a specification of φ90mm and a height of 300mm; Powder preparation: Saw the alloy prefabricated master ingot into small pieces, melt the prefabricated alloy small master ingot at 720℃ in a melting crucible by vacuum gas atomization powder making to prepare alloy melt. Evacuate the vacuum atomization melting chamber to 1*10 -2 Pa, argon gas is used for replacement treatment to keep the gas pressure at 4.0MPa; the molten alloy liquid passes through a nozzle, is crushed by gas atomization argon gas high pressure, and then is cooled and spheroidized to obtain aluminum alloy metal powder; the aluminum alloy metal powder is cooled to 25°C, sieved in an argon atmosphere, and then vacuum packaged; Laser melting: The powder with a particle size range of 15-53 μm after screening was subjected to aging heat treatment after laser melting to obtain the final molded part. A 10 mm × 10 mm × 10 mm cubic block was printed, and the alloy hardness was measured using a microhardness tester. After direct aging at 325 ° C / 6 h, the mechanical properties were tested using an ETM105D universal testing machine with a tensile rate of 1 mm / min.

[0029] Example 4 Laser melted Al-Mn-Sc-Zr alloy powder, by mass percentage, has a composition of Mn: 5.5%, Mg: 1.5%, Sc: 1.0%, Zr: 0.5%, Cu: 1.5%, Ti: 0.25%, Si: 1.0%, and the rest are Al and unremovable impurity elements.

[0030] Preparation of mother ingot: add pure aluminum ingot to the crucible in the medium frequency furnace at a temperature of 460°C; raise the temperature of the smelting chamber to 720°C until the pure aluminum ingot is melted; raise the temperature to 760°C, add Al-10Mn, Al-50Cu, Al-20Si and Al-5Ti to the resistance furnace, and keep warm for 10 minutes; then add A1-2Sc master alloy and Al-5Zr master alloy in sequence, and keep warm for 30 minutes after they are completely melted; reduce the power of the medium frequency furnace to reduce the temperature to 720°C, and add pure magnesium ingot at the same time; after the magnesium ingot is completely melted, keep warm for 10 minutes, add 0.1% by mass of Al-Ti-B wire to obtain molten aluminum alloy liquid; cast the molten aluminum alloy liquid into a prefabricated alloyed mother ingot with a specification of φ90mm and a height of 300mm; Powder preparation: Saw the alloy prefabricated master ingot into small pieces, melt the prefabricated alloy small master ingot at 740℃ in a melting crucible by vacuum gas atomization powder making to prepare alloy melt. Evacuate the vacuum atomization melting chamber to 1*10 -2 Pa, argon is used for replacement treatment to keep the gas pressure at 3.5MPa; the molten alloy liquid passes through a nozzle, is crushed by atomized argon gas under high pressure, and then is cooled and spheroidized to obtain aluminum alloy metal powder; the aluminum alloy metal powder is cooled to 25°C, sieved in an argon atmosphere and vacuum packaged.

[0031] Laser melting: The powder with a particle size range of 15-53 μm after screening was subjected to aging heat treatment after laser melting to obtain the final molded part. A 10 mm × 10 mm × 10 mm cubic block was printed, and the alloy hardness was measured using a microhardness tester. After direct aging at 325 ° C / 6 h, the mechanical properties were tested using an ETM105D universal testing machine with a tensile rate of 1 mm / min.

[0032] Comparative Example 1 Laser melted Al-Mn-Mg alloy powder has a composition of Mn: 4.75%, Mg: 1.35%, and the rest is Al and unremovable impurity elements, by mass percentage.

[0033] Preparation of mother ingot: add pure aluminum ingot to the crucible in the medium frequency furnace at a temperature of 460°C; raise the temperature of the smelting chamber to 720°C until the pure aluminum ingot melts; raise the temperature to 760°C, add Al-10Mn to the resistance furnace, and keep it warm for 10 minutes; reduce the power of the medium frequency furnace to reduce the temperature to 710°C, and add pure magnesium ingot; after the magnesium ingot is completely melted, keep it warm for 10 minutes, add 0.1% by mass of Al-Ti-B wire to obtain molten aluminum alloy liquid; cast the molten aluminum alloy liquid into a prefabricated alloyed mother ingot with a specification of φ90mm and a height of 300mm; Powder preparation: Saw the alloy prefabricated master ingot into small pieces, melt the prefabricated alloy small master ingot at 740℃ in a melting crucible by vacuum gas atomization powder making method to prepare alloy melt. Evacuate the vacuum atomization melting chamber to 0~10 -2 Pa, argon gas is used for replacement treatment to keep the gas pressure at 0.5~4MPa; the molten alloy liquid passes through a nozzle, is crushed by gas atomization argon gas high pressure, and then cooled and spheroidized to obtain aluminum alloy metal powder; after the aluminum alloy metal powder is cooled to 30°C, it is sieved in an argon atmosphere and then vacuum packaged; Laser melting: The powder with a particle size range of 15-53 μm after screening was subjected to aging heat treatment after laser melting to obtain the final molded part. A 10 mm × 10 mm × 10 mm cubic block was printed, and the alloy hardness was measured using a microhardness tester. After direct aging at 325 ° C / 6 h, the mechanical properties were tested using an ETM105D universal testing machine with a tensile rate of 1 mm / min.

[0034] Comparative Example 2 Laser melted Al-Mn-Mg alloy powder has a composition of Mn: 4.75%, Mg: 1.35%, Sc: 0.6%, Zr: 0.4%, and the rest is Al and unremovable impurity elements, by mass percentage.

[0035] Preparation of mother ingot: add pure aluminum ingot to the crucible in the medium frequency furnace at a temperature of 460°C; raise the temperature of the smelting chamber to 720°C until the pure aluminum ingot melts; raise the temperature to 760°C, add Al-10Mn to the resistance furnace, and keep it warm for 10 minutes; then add A1-2Sc master alloy and Al-5Zr master alloy in sequence, and keep it warm for 30 minutes after they are completely melted; reduce the power of the medium frequency furnace to reduce the temperature to 740°C, and add pure magnesium ingot; after the magnesium ingot is completely melted, keep it warm for 10 minutes, add 0.1% by mass of Al-Ti-B wire to obtain molten aluminum alloy liquid; cast the molten aluminum alloy liquid into a prefabricated alloyed mother ingot with a specification of φ90mm and a height of 300mm; Powder preparation: Saw the alloy prefabricated master ingot into small pieces, melt the prefabricated alloy small master ingot at 720℃ in a melting crucible by vacuum gas atomization powder making to prepare alloy melt. Evacuate the vacuum atomization melting chamber to 0~10 -2 Pa, argon gas is used for replacement treatment to keep the gas pressure at 0.5~4MPa; the molten alloy liquid passes through a nozzle, is crushed by gas atomization argon gas high pressure, and then cooled and spheroidized to obtain aluminum alloy metal powder; after the aluminum alloy metal powder is cooled to 30°C, it is sieved in an argon atmosphere and then vacuum packaged; Laser melting: The powder with a particle size range of 15-53 μm after screening was subjected to aging heat treatment after laser melting to obtain the final molded part. A 10 mm × 10 mm × 10 mm cubic block was printed, and the alloy hardness was measured using a microhardness tester. After direct aging at 325 ° C / 6 h, the mechanical properties were tested using an ETM105D universal testing machine with a tensile rate of 1 mm / min.

[0036] Comparative Example 3 Laser melted Al-Mn-Mg alloy powder has a composition of Mn: 5.5%, Mg: 1.35%, Sc: 0.6%, Zr: 0.5%, Si: 0.5%, and the rest is Al and unremovable impurity elements, by mass percentage.

[0037] Preparation of mother ingot: add pure aluminum ingot to the crucible in the medium frequency furnace at a temperature of 460°C; raise the temperature of the smelting chamber to 700°C until the pure aluminum ingot is melted; raise the temperature to 780°C, add Al-10Mn and Al-20Si to the resistance furnace, and keep warm for 10 minutes; then add A1-2Sc master alloy and Al-5Zr master alloy in turn, and keep warm for 30 minutes after they are completely melted; reduce the power of the medium frequency furnace to reduce the temperature to 720°C, and add pure magnesium ingot; after the magnesium ingot is completely melted, keep warm for 10 minutes, add 0.1% by mass of Al-Ti-B wire to obtain molten aluminum alloy liquid; cast the molten aluminum alloy liquid into a prefabricated alloyed mother ingot with a specification of φ90mm and a height of 300mm; Powder preparation: Saw the alloy prefabricated master ingot into small pieces, melt the prefabricated alloy small master ingot at 740℃ in a melting crucible by vacuum gas atomization powder making method to prepare alloy melt. Evacuate the vacuum atomization melting chamber to 0~10 -2 Pa, argon gas is used for replacement treatment to keep the gas pressure at 0.5~4MPa; the molten alloy liquid passes through a nozzle, is crushed by gas atomization argon gas high pressure, and then cooled and spheroidized to obtain aluminum alloy metal powder; after the aluminum alloy metal powder is cooled to 30°C, it is sieved in an argon atmosphere and then vacuum packaged; Laser melting: The powder with a particle size range of 15-53 μm after screening was subjected to aging heat treatment after laser melting to obtain the final molded part. A 10 mm × 10 mm × 10 mm cubic block was printed, and the alloy hardness was measured using a microhardness tester. After direct aging at 325 ° C / 6 h, the mechanical properties were tested using an ETM105D universal testing machine with a tensile rate of 1 mm / min.

[0038] Comparative Example 4 Laser melted Al-Mn-Mg alloy powder has a composition of Mn: 5.5%, Mg: 1.35%, Sc: 0.8%, Zr: 0.5%, Zn: 1.0%, Si: 0.5%, and the rest are Al and unremovable impurity elements, by mass percentage.

[0039] Preparation of mother ingot: add pure aluminum ingot to the crucible in the medium frequency furnace at a temperature of 500°C; raise the temperature of the smelting chamber to 750°C until the pure aluminum ingot is melted; raise the temperature to 760°C, add Al-10Mn and Al-20Si to the resistance furnace, and keep warm for 10 minutes; then add A1-2Sc master alloy and Al-5Zr master alloy in turn, and keep warm for 30 minutes after they are completely melted; reduce the power of the medium frequency furnace to reduce the temperature to 720°C, and add pure magnesium ingot and zinc ingot at the same time; after the magnesium ingot and zinc ingot are completely melted, keep warm for 10 minutes, add 0.1% by mass Al-Ti-B wire to obtain molten aluminum alloy liquid; cast the molten aluminum alloy liquid into a prefabricated alloyed mother ingot with a specification of φ90mm and a height of 300mm; Powder preparation: Saw the alloy prefabricated master ingot into small pieces, melt the prefabricated alloy small master ingot at 740℃ in a melting crucible by vacuum gas atomization powder making method to prepare alloy melt. Evacuate the vacuum atomization melting chamber to 0~10 -2 Pa, argon gas is used for replacement treatment to keep the gas pressure at 0.5~4MPa; the molten alloy liquid passes through a nozzle, is crushed by gas atomization argon gas high pressure, and then cooled and spheroidized to obtain aluminum alloy metal powder; after the aluminum alloy metal powder is cooled to 30°C, it is sieved in an argon atmosphere and then vacuum packaged; Laser melting: The powder with a particle size range of 15-53 μm after screening was subjected to aging heat treatment after laser melting to obtain the final molded part. A 10 mm × 10 mm × 10 mm cubic block was printed, and the alloy hardness was measured using a microhardness tester. After direct aging at 325 ° C / 6 h, the mechanical properties were tested using an ETM105D universal testing machine with a tensile rate of 1 mm / min.

[0040] Comparative Example 5 Laser melted Al-Mn-Sc-Zr alloy powder has a composition of Mn: 5.0%, Mg: 1.35%, Sc: 0.4%, Zr: 0.2%, Cu: 0.1%, Si: 0.6%, and the rest are Al and unremovable impurity elements, by mass percentage.

[0041] Preparation of mother ingot: add pure aluminum ingot to the crucible in the medium frequency furnace at a temperature of 460°C; raise the temperature of the smelting chamber to 700°C until the pure aluminum ingot is melted; raise the temperature to 740°C, add Al-10Mn, Al-50Cu, Al-20Si and Al-5Ti to the resistance furnace, and keep warm for 10 minutes; then add A1-2Sc master alloy and Al-5Zr master alloy in turn, and keep warm for 30 minutes after they are completely melted; reduce the power of the medium frequency furnace to reduce the temperature to 720°C, and add pure magnesium ingot at the same time; after the magnesium ingot is completely melted, keep warm for 10 minutes, add 0.1% by mass of Al-Ti-B wire to obtain molten aluminum alloy liquid; cast the molten aluminum alloy liquid into a prefabricated alloyed mother ingot with a specification of φ90mm and a height of 300mm; Powder preparation: Saw the alloy prefabricated master ingot into small pieces, melt the prefabricated alloy small master ingot at 720℃ in a melting crucible by vacuum gas atomization powder making to prepare alloy melt. Evacuate the vacuum atomization melting chamber to 1*10 -2 Pa, argon gas is used for replacement treatment to keep the gas pressure at 4.0MPa; the molten alloy liquid passes through a nozzle, is crushed by gas atomization argon gas high pressure, and then is cooled and spheroidized to obtain aluminum alloy metal powder; the aluminum alloy metal powder is cooled to 25°C, sieved in an argon atmosphere, and then vacuum packaged; Laser melting: The powder with a particle size range of 15-53 μm after screening was subjected to aging heat treatment after laser melting to obtain the final molded part. A 10 mm × 10 mm × 10 mm cubic block was printed, and the alloy hardness was measured using a microhardness tester. After direct aging at 325 ° C / 6 h, the mechanical properties were tested using an ETM105D universal testing machine with a tensile rate of 1 mm / min.

[0042] Comparative Example 6 Laser melted Al-Mn-Sc-Zr alloy powder has a composition, by mass percentage, of Mn: 5.0%, Mg: 1.0%, Sc: 0.4%, Zr: 0.2%, Cu: 0.05%, Ti: 0.05%, Si: 0.3%, and the rest are Al and unremovable impurity elements.

[0043] Preparation of mother ingot: add pure aluminum ingot to the crucible in the medium frequency furnace at a temperature of 460°C; raise the temperature of the smelting chamber to 720°C until the pure aluminum ingot is melted; raise the temperature to 760°C, add Al-10Mn, Al-50Cu, Al-20Si and Al-5Ti to the resistance furnace, and keep warm for 10 minutes; then add A1-2Sc master alloy and Al-5Zr master alloy in sequence, and keep warm for 30 minutes after they are completely melted; reduce the power of the medium frequency furnace to reduce the temperature to 720°C, and add pure magnesium ingot at the same time; after the magnesium ingot is completely melted, keep warm for 10 minutes, add 0.1% by mass of Al-Ti-B wire to obtain molten aluminum alloy liquid; cast the molten aluminum alloy liquid into a prefabricated alloyed mother ingot with a specification of φ90mm and a height of 300mm; Powder preparation: Saw the alloy prefabricated master ingot into small pieces, melt the prefabricated alloy small master ingot at 720℃ in a melting crucible by vacuum gas atomization powder making to prepare alloy melt. Evacuate the vacuum atomization melting chamber to 1*10 -2 Pa, argon gas is used for replacement treatment to keep the gas pressure at 4.0MPa; the molten alloy liquid passes through a nozzle, is crushed by gas atomization argon gas high pressure, and then is cooled and spheroidized to obtain aluminum alloy metal powder; the aluminum alloy metal powder is cooled to 25°C, sieved in an argon atmosphere, and then vacuum packaged; Laser melting: The powder with a particle size range of 15-53 μm after screening was subjected to aging heat treatment after laser melting to obtain the final molded part. A 10 mm × 10 mm × 10 mm cubic block was printed, and the alloy hardness was measured using a microhardness tester. After direct aging at 325 ° C / 6 h, the mechanical properties were tested using an ETM105D universal testing machine with a tensile rate of 1 mm / min.

[0044] Table 1 is a comparative test of the mechanical properties of materials prepared by laser melting in the embodiment and the comparative example, wherein the mechanical properties were tested using an ETM105D universal testing machine at a tensile rate of 1 mm / min.

[0045] Table 1 Comparison of mechanical properties from Figure 1 It can be seen that (a) is the metallographic image of the Al-Mn-Mg alloy powder after printing, which has a large number of defects such as lack of fusion and a large number of microcracks; (b) is the metallographic image of the Al-Mn-Mg-Sc-Zr alloy powder after printing, which has certain holes; (c) is the metallographic image of the Al-Mn-Mg-Sc-Zr alloy powder with the optimal composition ratio after printing, with no cracks, no pores, and high density; (d) is the metallographic image of the Al-Mn-Mg-Sc-Zr alloy powder with excessive Mn, Sc, Zr, Cu, and Ti added after printing, with no cracks, a small amount of pores, and high density.

[0046] Table 2 Figure 2 EDS data statistics at each point Combination Figure 2 From Table 2, we can see the Mg2Si, Al6Mn, and Mg5Si6 phases distributed in the matrix.

[0047] In the embodiments, only SLM powder is used as an example, and powders and wires with other particle sizes or uses can be prepared.

[0048] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, those skilled in the art will also intend to include these modifications and variations if they fall within the scope of the claims of the present invention and their equivalents.

Claims

1. An Al-Mn-Sc-Zr aluminum alloy powder for additive manufacturing, comprising the following components by mass percentage: Mn: 4.0~7.0%, Mg: 0.5~3.0%, Cu: 0.2~1.5%, Ti: 0.05~0.2%, Sc: 0.4~1.0%, Zr: 0.2~0.8%, Si: 0.2~0.8%, Fe: <0.15%, the rest are A1 and non-removable impurities; the mass percentage ratio of Sc and Zr is 2:

1.

2. The Al-Mn-Sc-Zr aluminum alloy powder for additive manufacturing according to claim 1, characterized in that: In terms of mass percentage, it is composed of the following components: Mn: 4.5~5.5%, Mg: 1.0~1.5%, Cu: 0.2~1.5%, Ti: 0.05~0.2%, Sc: 0.4~1.0%, Zr: 0.2~0.5%, Si: 0.5~0.8%, Fe: <0.15%, and the rest are A1 and non-removable impurity elements.

3. The Al-Mn-Sc-Zr aluminum alloy powder for additive manufacturing according to claim 1 or 2, characterized in that: In terms of mass percentage, Mg+Si≥1.85%, Sc+Zr≥0.6%.

4. A method for preparing Al-Mn-Sc-Zr aluminum alloy powder for additive manufacturing according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) Add pure aluminum ingots into the crucible in the medium frequency furnace at a temperature of 460°C; (2) Raise the temperature of the smelting chamber to 720°C~740°C until the pure aluminum ingot is melted; (3) Raise the temperature to 740-760°C, add Al-10Mn, Al-50Cu, Al-20Si and Al-5Ti master alloys to the resistance furnace in turn, keep warm for 10 min, then add Al-2Sc master alloy and Al-5Zr master alloy in turn, keep warm for 30 min after they are completely melted; (4) Lower the power of the medium frequency furnace to reduce the temperature to 710~720℃ and add pure magnesium ingot; (5) After the magnesium ingot is completely melted, keep it warm for 10 minutes, add 0.1% by mass of Al-Ti-B wire to obtain molten aluminum alloy liquid; (6) The molten aluminum alloy is water-cooled and semi-continuously cast into a prefabricated alloyed mother ingot with a specification of φ90mm-φ720.

5. The preparation method according to claim 4, characterized in that: The alloyed mother ingot is made into powder or wire.

6. Use of the powder prepared by the preparation method according to claim 5 in additive manufacturing.

7. The use according to claim 6, characterized in that: The application in additive manufacturing is to make the alloyed mother ingot into aluminum alloy metal powder for laser melting printing or into wire for arc additive manufacturing.

8. The use according to claim 7, characterized in that: Alloyed master ingots are made into aluminum alloy metal powder for laser melting printing: the alloyed master ingots are sawn into small pieces, and the prefabricated alloyed small master ingots are melted at 700℃~760℃ in a melting crucible by vacuum gas atomization to prepare alloy melt, and the prefabricated alloy metal powder is obtained after gas atomization cooling. After the aluminum alloy metal powder is cooled to 25℃~60℃, it is sieved in an argon atmosphere and vacuum packaged.

9. The use according to claim 8, characterized in that: The vacuum atomization melting chamber is evacuated to 0~10 -2 Pa, argon gas is used for replacement treatment to keep the gas pressure between 0.5 and 6 MPa; the atomization gas pressure is in the range of 0.5 MPa to 4 MPa.

10. The use according to any one of claims 7 to 9, characterized in that: The particle size range of aluminum alloy metal powder is 15~53μm.

Citation Information

Patent Citations

  • High-intensity aluminum alloy powder material for manufacturing additional material and preparation method thereof

    CN107502795A

  • A high-strength aluminum alloy powder and its application in 3D printing and its 3D printing method

    CN114277285B

  • High-strength corrosion-resistant aluminum alloy for 3D printing, preparation method and printing process

    CN115141955A

  • 3D printing high-strength Al-Mg-Mn-Sc-Zr alloy powder and forming method thereof

    CN115354199A

Cited By

  • High-strength and high-conductivity aluminum alloy powder for selective laser melting and low-residual-stress forming process of high-strength and high-conductivity aluminum alloy powder

    CN121780951A